2020
DOI: 10.1051/0004-6361/201937412
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating flicker noise in high-precision photometry

Abstract: Context. In photometry, the short-timescale stellar variability (“flicker”), such as that caused by granulation and solar-like oscillations, can reach amplitudes comparable to the transit depth of Earth-sized planets and is correlated over the typical transit timescales. It can introduce systematic errors on the inferred planetary parameters when a small number of transits are observed. Aims. The objective of this paper is to characterize the statistical properties of the flicker noise and quantify its impact … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 66 publications
5
36
0
Order By: Relevance
“…One mechanism might be the suppression of granulation within the boundaries of a spot, which reduces the number of granules contributing to F 8 and thereby increases F 8 . The solar F 8 has been shown to be independent of the solar cycle (Bastien et al 2013;Sulis et al 2020), suggesting that activity levels up to solar levels do not affect F 8 . We have not attempted to model this possibility for greater activity levels in the present work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One mechanism might be the suppression of granulation within the boundaries of a spot, which reduces the number of granules contributing to F 8 and thereby increases F 8 . The solar F 8 has been shown to be independent of the solar cycle (Bastien et al 2013;Sulis et al 2020), suggesting that activity levels up to solar levels do not affect F 8 . We have not attempted to model this possibility for greater activity levels in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…Another motivation for understanding stellar flicker is to constrain the noise present in planetary transit measurements. Studies have shown that stellar granulation produces a non-negligible effect in the noise present during observations of planetary transits, introducing, e.g., uncertainty in planetary radius measurements of a few percent (Chiavassa et al 2017;Morris et al 2020), or even up to 10% (Sulis et al 2020), depending on the observation being modeled. One cause of this noise is that the granulation provides one of many deviations from a perfect black body, affecting signals especially during spectroscopic observations.…”
Section: Introductionmentioning
confidence: 99%
“…The damping time scale for this process is τ = 2 Q/ω0 and the standard deviation of the process is σGP = √ S0 ω0 Q. The Dataset module includes a function to plot the fast Fourier transform (FFT) of the residuals from the best-fit transit or eclipse model in log-log space so that the user can look for a slope or peaks in the power spectrum due to stellar granulation or oscillations (Sulis et al 2020).…”
Section: Ksho(τmentioning
confidence: 99%
“…This versatile and highly reproducible analysis shows that space weather cannot be left out of considerations for planetary habitability in stellar systems. It carries both value and promise: consider the European Space Agency CHEOPS (Characterizing Exoplanet Satellite) mission, for example ( e.g., Sulis et al 2020). The mission is designed to characterize only selected, confirmed exoplanets, ranging from super-Earth to Neptune sizes, aiming toward studies that extend into their potential atmospheres.…”
Section: Discussionmentioning
confidence: 99%